2011
DOI: 10.1097/qai.0b013e318211b43b
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Long-Term Adherence to Highly Active Antiretroviral Therapy in Senegal Using Latent Class Analysis

Abstract: This study shows that an overall good adherence can be obtained in the long term in Senegal. LCA suggests a better adherence for women and points out a large subsample of patients with intermediate level of adherence behavior who are at risk for developing resistance to antiretroviral drugs. This study warrants further research into gender issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 39 publications
2
21
1
2
Order By: Relevance
“…In our study 6% of patient appointments were attended with a delay of one or more days. Although previous studies have suggested that adherence might decline with time on ART [13], in our analysis, both the proportion of appointments attended with delay and the interval between successive clinic visits remained almost constant over time since treatment initiation. The median treatment duration of study patients was 26 months and 75% of individuals had received therapy for less than 45 months.…”
Section: Discussioncontrasting
confidence: 73%
“…In our study 6% of patient appointments were attended with a delay of one or more days. Although previous studies have suggested that adherence might decline with time on ART [13], in our analysis, both the proportion of appointments attended with delay and the interval between successive clinic visits remained almost constant over time since treatment initiation. The median treatment duration of study patients was 26 months and 75% of individuals had received therapy for less than 45 months.…”
Section: Discussioncontrasting
confidence: 73%
“…In a high risk urban population in sub-Saharan Africa 38% of patients were non-adherent to HAART at some point during their treatment [10]. Furthermore, adherence to HAART appears to decrease steadily over time but may vary by gender and HAART regimen [11]. In Rwanda, where HIV prevalence is 2.9% and approximately 70,047 HIV+ persons receive HAART, there has been limited study of both HAART adherence rates and factors associated non-adherence.…”
Section: Introductionmentioning
confidence: 99%
“…Third, LCA was used as a data reduction technique by which to categorize individuals into their most likely class membership along the spectrum of the SUMIC Syndemic (non-observable latent variable, based on the latent conditions of active substance use, mental illness, and familial conflict non-negotiation; Bastard et al, 2011; Ahn et al, 2008; Collins & Lanza, 2010). Fourth, the syndemic classes were regressed on the three relevant correlates: sex, viral suppression (UVL), and acute care non-utilization (ACN).…”
Section: Methodsmentioning
confidence: 99%
“…However, assessment of Syndemic Theory in a sample of all African-American HIV-positive persons with a history of substance use has not been conducted to our knowledge. Also, unlike these studies, the present analyses utilized latent class analyses, which has been applied in several previous investigations of Syndemic Theory (Bastard et al, 2011; Ahn et al, 2008; Collins & Lanza, 2010). Therefore, the purpose of this study was to examine the presence and correlates of a potential latent syndemic in a cohort of African-American PLHIV.…”
Section: Introductionmentioning
confidence: 99%